Prisotnost različnih genotipov bakterije Clostridium difficile pri hospitaliziranih bolnikih v Sloveniji med dvomesečnim zimskim obdobjem - Rupnik, Maja (Zdravniški vestnik, 2013)
Background: Clostridium difficile is an important cause of nosocomial diarrhoea. Strains arefurther differentiated into PCR ribotypes, andsome ribotypes (e.g. 027) are often associated with outbreaks, increased disease severity and increased mortality. Here we describe the diversity of C. difficile among human isolates in Slovenia. Methods: All eight microbiological diagnostic laboratories providing C. difficile diagnostics in Slovenia have participated. Isolates from two month- winter period were collected and ribotyped.The following data were also collected from the laboratories: number of all tested samples, number of all positive samples, and patient age and gender. Results: In a two-month period, altogether 860 samples were tested for C. difficile in all participating laboratories. Of those, 154 (17.9 %) samples from 125 patients were positive. The percentage of positive samples in different laboratories ranged from 13.3 to 43.2%. Two out of eight laboratoriesdid not have positive samples. C. difficile strains(n= 149) were grouped into 35 ribotypes. However, 57.7% of all strains belonged only to two PC Rribotypes (027 and 014/020). PCR ribotype 027 was not present in Slovenia until 2010, but was in this study the most prevalent PCR ribotype and present mainly in the northeast region.Conclusions: There is a substantial diversity of C. difficile ribotypes in Slovenia. A high prevalence of ribotype 027 and a high percentage of positive samples in some laboratories indicate the presence of C. difficile outbreaks.
Keywords: bolnišnične okužbe; Clostridium difficile; microbiology diagnostics; mikrobiološka diagnostika; nosocomial infections